1987
DOI: 10.1136/jnnp.50.12.1572
|View full text |Cite
|
Sign up to set email alerts
|

The aetiology of mirror writing: a new hypothesis.

Abstract: SUMMARY Twenty-eight cases of mirror writing were seen during a period of three and a half years. These consisted of 12 patients with essential tremor, nine with Parkinson's disease, three with spino-cerebellar degeneration and four other cases. There were no cases of hemiparesis, aphasia, apraxia, agnosia or confusion. Fragmentary reversals were excluded from this study. Since essential tremor, Parkinsonian tremor and cerebellar tremor can be abolished by a stereotaxic produce applied to the thalamus, a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
5

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 7 publications
0
23
0
5
Order By: Relevance
“…This omission may have resulted in an underestimation of the prevalence of MW. Moreover, two cases have been reported [2,22] of left-hand MW following right hemisphere lesion. Yet, the performance of right-hemisphere damaged patients has been ignored in group studies.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This omission may have resulted in an underestimation of the prevalence of MW. Moreover, two cases have been reported [2,22] of left-hand MW following right hemisphere lesion. Yet, the performance of right-hemisphere damaged patients has been ignored in group studies.…”
mentioning
confidence: 96%
“…We propose that the diagnosis of MW should be limited to the reversal of whole words, multi-digit numbers and full sentences, which reveal a disorder in coding the correct direction of writing rather than an inability to accomplish the correct spatial orientation of single letters. frequency of MW in an unselected series of hemiplegic patients varies between 2.4% [8] to 13% [22]. A higher frequency (24%) is reported when only patients with left hemisphere lesions were considered [23], however, none of the available studies on the frequency of mirror writing specifies the selection criteria of the sample [8,17,21,22].…”
mentioning
confidence: 97%
“…Studies among the elderly in China and Japan have shown an increase in mirror writing in relation to cerebral damage and cognitive dysfunction [3,4]. A high prevalence of mirror writing has been described in patients with essential tremor, Parkinson disease, and cerebellar disorders [2].…”
Section: Discussionmentioning
confidence: 99%
“…Mirror writing may be transient or long lasting, and may affect single letters or characters, whole words or sentences. Although mirror writing occurs both spontaneously and pathologically, it is generally associated with cerebrovascular lesions in the dominant hemisphere [2].…”
Section: Introductionmentioning
confidence: 99%
“…The downwards writing observed in this patient implies that characteristics of mirror writing at the level of a connected script are language-specific [2,6,7] . The modern Korean script is typically written in the left-to-right direction, as are IndoEuropean scripts such as English.…”
Section: Discussionmentioning
confidence: 99%